Innovation of the Mitra Desa Application as a Facilitation Tool for the Issuance of Business Identification Numbers in Supporting the Investment Competitiveness of Wonogiri Regency - Akbar Kurnia Romadhon; Galih Wahyu Pradana; Muhammad Farid Ma’ruf; Deby Febriyan Eprilianto (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Public service is a key indicator of government performance in meeting community needs effectively and efficiently. In the implementation of business licensing services through the Online Single Submission (OSS) system, several challenges remain at the rural level, including low digital literacy, limited access to technology, and complex procedures. To address these issues, the Wonogiri Regency DPMPTSP initiated the Mitra Desa Application Innovation to facilitate the issuance of Business Identification Numbers (NIB) through assistance provided by village officials. This study employed a descriptive qualitative approach using Utomo’s (2020) innovation indicators. The results of the study indicate that the compatibility of the Mitra Desa Application Innovation is reflected in its alignment with public service policies, community needs, and its support for licensing services and regional investment competitiveness. The innovation incubation process was carried out gradually through preparation, testing, and system improvement despite limitations in resources. The replication aspect shows that this innovation is an original initiative of the Wonogiri Regency DPMPTSP and not an imitation of other innovations, while also having the flexibility to be implemented in other regions according to local conditions. In terms of dissemination and diffusion, the innovation was spread through socialization, technical guidance, and collaboration among various stakeholders to expand its utilization. Meanwhile, the institutionalization aspect indicates that the innovation has been integrated into daily service practices through system maintenance, monitoring, and the continuous involvement of various parties.